Utilization of Zn Powder as a Precursor in Synthesis of rGO/ZnO Composite for Decolorization of Batik Wastewater - Wahyuni, Dwiria; Mariani, Mariani; Asri, Asifa; Arsyad, Ya Muhammad (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2026)
Batik wastewater contains high concentrations of synthetic dyes, significantly contributing to aquatic pollution. Photocatalysis is a promising method for degrading such dyes in textile effluents. This study aims to develop rGO/ZnO composites using zinc (Zn) powder as a precursor for photocatalytic applications. Reduced graphene oxide (rGO) was used as a substrate for ZnO particle formation. The composites were prepared by reacting Zn powder with rGO at varying loadings (5% and 10% by mass) in a neutral aqueous solution, followed by thermal treatment at 250 °C for 1 hour to facilitate Zn oxidation. The photocatalytic performance was evaluated by applying different masses of rGO/ZnO (0.2, 0.4, and 0.8 g) to degrade batik wastewater. Surface morphology and elemental composition were characterized using SEM-EDS. SEM analysis showed that rGO has a sheet-like structure, while ZnO exhibits spherical morphology. EDS confirmed the presence of Zn, C, and O as major elements with Nb impurity was identified in the composite. The carbon-to-oxygen (C/O) ratio increased after composite formation, reaching 4.23 for rGO/ZnO 5% and 3.79 for rGO/ZnO 10%. XRD characterization of rGO/ZnO confirms the presence of ZnO in the composite, with residual Zn peaks indicating incomplete oxidation of the Zn precursor. Photocatalytic activities modeled using pseudo-first-order kinetics reveal the 10% rGO/ZnO composite (0.8 g) shows the degradation efficiency of 67.91%, with a rate constant of 0.1623 h⁻¹. The efficiency may be affected by the complex nature of batik wastewater, particularly wax and resin residues that hinder photocatalytic activity. In conclusion, these findings highlight the potential of Zn powder as a precursor in the synthesis of rGO/ZnO composites with concentration of rGO and the mass variation of rGO/ZnO in the treatment of Batik wastewater affect the photocatalytic activity.